1990
DOI: 10.2989/025776190784378835
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution, diet and possible impact of the invasive European shore crabCarcinus maenas(L.) along the South African coast

Abstract: The crab Carcinus maenas (L.) has an endemic distribution along the European Atlantic coastline but has been accidentally introduced into intertidal habitats in several parts of the world. Its discovery al the Cape Peninsula in South Africa is recorded here. The crab is well established in Table Bay harbour and the population is at least seven years old. From here it has spread 117 km north and 10 km south. Populations on the open coast are more recently established. The crab feeds on a wide range of intertid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 7 publications
5
63
0
Order By: Relevance
“…The species has spread northwards and southwards, and has been recorded in eastern North America and South Australia, although permanent populations were unlikely to become established in some locations (Carlton and Cohen 2003). However, a global dispersion has been taking place for the last 25 years to areas as distant as Japan (Sakai 1986), western North America (Cohen et al 1995), South Africa (Le Roux et al 1990), and the Patagonian Atlantic coast. In regard to the latter, the species was found along the central coasts of San Jorge Gulf (45掳55' S) in 2001 (Vinuesa 2005), and in Camarones Bay, north to San Jorge Gulf (approximately 44掳54' S), in 2003 (Hidalgo et al 2005).…”
mentioning
confidence: 99%
“…The species has spread northwards and southwards, and has been recorded in eastern North America and South Australia, although permanent populations were unlikely to become established in some locations (Carlton and Cohen 2003). However, a global dispersion has been taking place for the last 25 years to areas as distant as Japan (Sakai 1986), western North America (Cohen et al 1995), South Africa (Le Roux et al 1990), and the Patagonian Atlantic coast. In regard to the latter, the species was found along the central coasts of San Jorge Gulf (45掳55' S) in 2001 (Vinuesa 2005), and in Camarones Bay, north to San Jorge Gulf (approximately 44掳54' S), in 2003 (Hidalgo et al 2005).…”
mentioning
confidence: 99%
“…Crabs were collected in traps and by hand in (a, upper panels) Menai Straits, Gwynedd, UK (n = 5096), and (b, lower panels) Barkley Sound, British Columbia, Canada (n = 1792) 1982). However, seawater temperatures in the Menai Strait (Harvey 1972) and Barkley Sound (Bamfield Marine Sciences Centre, Ocean News Records) are similar, and in South Africa, where water temperatures are warmer and the growing season is longer, the crabs are no larger than their native counterparts (Le Roux et al 1990). Prey items are also plentiful in both areas, and there is little evidence to suggest that growth in crabs from Europe is limited by food availability (Klein Breteler 1975, Berrill 1982.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the maximum size attained by green crabs Carcinus maenas appears highly consistent, both in its native range and in locations where it has become established (Australia, east coast of North America, Patagonia, South Africa) and is classified as an invasive species (Ropes 1968, Le Roux et al 1990, Hidalgo et al 2005, Audet et al 2008 reported maximum sizes. In general, females were smaller than males, and, although they may reach >90 mm CW (J. Drewery, FRS Marine Labs, pers.…”
Section: Discussionmentioning
confidence: 99%
“…The green crab appeared to be the general top predator in the absence of Buccinum sp. It is well known as a voracious carnivore, feeding on mussels, clams, snails, worms, barnacles, seaweed, isopods and other crustaceans (Hardwick-Witman 1985;le Roux et al 1990;Smallegange and van de Meer 2003). Our results supported this view, as C. maenas (…”
Section: Edulismentioning
confidence: 99%